S-21: La Machine De Mort Khmere Rouge . S-21: The Khmer Rouge Killing Machine - Panh, Rithy (INA France, 2002)
Verzio FF For years Cambodian society has has lived in hope that those responsible for the Khmer Rouge genocide could be brought to trial. This is the context in which Rithy Panh decided to confront the memories of victims who managed to escape with those of their former torturers. For more than two years he searched for the people involved, and tried to persuade them to meet at Tuol Sleng, the torture center in Phnom Penh where, 25 years ago, some of them were plunged into horrifying everyday reality, and others served the machinery of programmed dehumanization and extermination. This documentary was shot at S21 in Phnom Penh, now a genocide museum, but once the country's main state security office. Here, between 1975 and 1977, Pol Pot's regime sanctioned the interrogation, torture and execution of untold thousands of people. Van Nath, a painter and one of the death camp's few survivors, returns with Panh to the rooms where he was beaten and starved. Also returning are a number of S21 prison guards, the very men who tortured Nath and thousands of others. The reconstitution of shared memory after the horror of the genocide is attempted by bringing individual memories face-to-face.